A dual-functional supramolecular hydrogel based on a spiropyran–galactose conjugate for target-mediated and light-controlled delivery of microRNA into cells. Issue 84 (6th October 2016) - Xiao, Xiao; Hu, Jing; Wang, Xingxing; Huang, Lei; Chen, Yingjie; Wang, Wei; Li, Jinbo; Zhang, Yan
Abstract : A dual-functional supramolecular hydrogel was developed for light-controlled release of miRNA and target-mediated delivery of miRNA into cells. Abstract : A supramolecular hydrogel formed by spiropyran conjugated galactose was developed for light-controlled release of miR-122 and target-mediated delivery of the miRNA into HepG2 cells cultured on top of the gel.